2021
DOI: 10.3855/jidc.15484
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Novel SARS-CoV-2 variants in India: second wave

Abstract: Introduction: Globally South-East Asia reported 40% of SARS-CoV-2 infected cases in the fourth week of April 2021. It continued to show an increase with India accounting for 50% of cases worldwide and 30% of global deaths. Genomic surveillance should continue at a rapid pace because of the continuously evolving nature of the virus. The time period of sample collection from the Global Initiative on Sharing All Influenza Data database was concurrent with the surge in new cases seen in the Indian subcontinent.&#x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The authors analyzed viral genomic sequences retrospectively and observed a similar pattern in the rise of the B.1.617 lineage, mainly the B.1.617.2 variant, in Delhi before the second wave [ 10 ]. A B.1.617.2-driven second wave was also reflected in the analysis of viral genomic sequences performed by Adiga and Nayak in 2021 [ 43 ]. We recently used our prediction model prospectively during the initial rise of cases caused by the Omicron strain in South Africa, which indicated an upcoming wave with very high transmissibility but limited lethality [ 4 ].…”
Section: Discussionmentioning
confidence: 95%
“…The authors analyzed viral genomic sequences retrospectively and observed a similar pattern in the rise of the B.1.617 lineage, mainly the B.1.617.2 variant, in Delhi before the second wave [ 10 ]. A B.1.617.2-driven second wave was also reflected in the analysis of viral genomic sequences performed by Adiga and Nayak in 2021 [ 43 ]. We recently used our prediction model prospectively during the initial rise of cases caused by the Omicron strain in South Africa, which indicated an upcoming wave with very high transmissibility but limited lethality [ 4 ].…”
Section: Discussionmentioning
confidence: 95%
“…This may be explicable because position 478 is within the receptor binding domain (RBD), and it had a high level of mutations in summer of 2020 [ 69 ] continuing through later in 2021 when the T478K mutation emerged as a characteristic mutation of the Delta lineage [ 66 ]. Similarly E484Q has been a characteristic mutation in the Delta lineage, but E484K has been an aspect of other pre-Delta, such as Beta and some Alpha sublineages [ 70 , 71 , 72 ]. Similarly, P681H was found in the highly prevalent Alpha lineage [ 73 ], and P681R was found in the Kappa and then later Delta lineage [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, another site with frequent mutations, site 484, where E484K, E484Q, and E484A mutations associated with antibody escape have been found [ 71 ], does not have high attention. The low attention at position 484 in the disease severity model may suggest that the site does not have a significant role in determining virulence rather than antibody evasion [ 26 , 70 , 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…[122] Similarly E484Q has been a characteristic mutation in the Delta lineage, but E484K has been an aspect of other pre-Delta, such as Beta and some Alpha sublineages. [126]–[128] Similarly, P681H was found in the highly prevalent Alpha lineage [129], and P681R was found in the Kappa and then later Delta lineage. [130] Accordingly, it may be the case that a consistently high attention suggests that the model pays attention to the site because it was not a point of variation at early time points.…”
Section: Resultsmentioning
confidence: 99%